Detection of nptII Gene and 35SCaMV Promoter in Tomatoes (Solanum lycopersicum L.) - Suratman, A.; Ughude, J. O.; ., Sismindari (Fakultas Farmasi, Universitas Gadjah Mada, 2013)
The detection of nptII (kanamycin resistance) as a transgenic marker gene and 35SCaMV as promoter in tomatoes has been carried out. DNA from tomatoes samples was isolated using PureLinkTM plant total DNA purification kit. The purity of DNA samples was estimated using UV-Vis spectrophotometry at 260 nm and 280 nm. They gave an absorbance ratio (A260/A280) of 1.74-1.79 which indicated its purities. The quality of the DNA was confirmed by a clear and thick band, as analyzed in 0.8% agarose gel electrophoresis. In order to identify the transgenic tomatoes, a 786-bp fragment of the nptII gene and a 86-bp fragment of 35SCaMV promoter were amplified using polymerase chain reaction (PCR). PCR reaction was prepared at optimum condition, namely annealing temperature at 56Â°C and 55Â°C for nptII gene and 35SCaMV promoter, respectively and 300 ng of DNA template. The PCR results were visualized on 2% agarose gel electrophoresis. The results showed that one of three tomatoes (code ST2) contains 35SCaMV promoter and no tomatoes contain nptII gene, indicating that ST2 is transgenic tomato.Key words: tomatoes, PCR, nptII, 35SCaMV